Application of Serial Picture Media to Short Story Writing Learning for Fifth Grade Students of SD Swasta GKPS No. 1 Pematang Siantar - Saragih, Mery Chris Isabella; Sianturi, Eduardo; Karo-karo, Romaida (Lembaga Riset Mutiara Akbar, 2025)
This study aims to describe the improvement of students’ short story writing skills through the application of serial picture media in the fifth-grade class of SD Swasta GKPS No. 1 Pematang Siantar. The background of this research is the students' low ability in writing short stories due to the lack of visual media used during the learning process. This research employed a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest model. The sample consisted of 13 students. Instruments included multiple-choice tests and a rubric for assessing short story writing. The pretest results showed an average score of 57.69, which was below the Minimum Mastery Criteria (KKM). After implementing the serial picture media, the posttest average increased to 85.77. Normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The paired sample t-test yielded a significance value of 0.00 < 0.05, thus Ha was accepted. These results demonstrate that serial picture media significantly enhance students’ short story writing skills. Therefore, this visual media proves to be effective in supporting Indonesian language learning, particularly in narrative writing skills.